DNA methylation dysregulations in valvular atrial fibrillation. Issue 9 (28th August 2017) - Shen, Kangjun; Tu, Tao; Yuan, Zhaoshun; Yi, Jiangfeng; Zhou, Yangzhao; Liao, Xiaobo; Liu, Qiming; Zhou, Xinmin
Abstract : Background: The epigenetic changes underlying the development of atrial fibrillation (AF) remain incompletely understood. Limited evidence suggests that abnormal DNA methylation might be involved in the pathogenesis of AF. In the present study, we evaluated the methylation status of genomic DNA from myocardial tissue in AF patients and sinus rhythm (SR) patients systematically. Hypothesis: DNA methylation dysregulations will be associated with valvular AF. Methods: Right atrial myocardial tissue was obtained from rheumatic valvular patients who had undergone valve replacement surgery (SR group, n = 10; AF group, n = 10). The global DNA methylation level, the promoter methylation level of the natriuretic peptide receptor‐A gene ( NPRA ), and its correlation with the mRNA expression level of DNA methyltransferase genes were detected. Results: The global DNA methylation level was significantly higher in the AF group than in the SR group ( P < 0.05). The NPRA mRNA expression was decreased and the NPRA gene was hypermethylated in the AF group ( P < 0.05). Meanwhile, the NPRA mRNA expression level has a negative correlation with the mean methylation level in the promoter region of the NPRA gene. Conclusions: DNA methylation dysregulations may be relevant in the pathogenesis of AF. DNA methyltransferase 3B likely plays an essential role in the DNA methylation dysregulations in AF.